Nodal governance: toward a better understanding of node relationships in local security governance - Quéro, Yann-Cédric (Policing and society, 2019)
This article explores the intricacies of the local security network in France, identifying local security actors (nodes) in order to trace their formal and informal exchanges. We outline the workings of nodal governance by looking at the different groups created informally within the local security network to reveal how resources are exchanged between nodes. Three categories of nodes are identified: a first are the most involved nodes, those who lead the local security network; a second are security actors who, while active, do not participate at the same level as the leading team; the third are nodes that use more security than they provide. The characteristics of the first group are similar to those of the super structural nodes discussed by Burris, Drahos, and Shearing in 2005. The main characteristics of the operating mechanisms of these superstructural nodes are discussed.